Evaluating the Implementation of NCE Primary Education Programme in College of Education in Nigeria - Samuel, Jeremiah; Okodoko, Diepreye (Richtmann Publishing, 2012)
This study evaluated the implementation of NCE Primary Education Programme in colleges of Education in Nigeria.The study was guided by three research questions and corresponding hypotheses. The population was made up of 127 PrimaryEducation Studies lecturers in five colleges of Education in south-south geopolitical zone of Nigeria. The sample comprised of 83lecturers in four colleges of education in the area. The instrument used for the study was Evaluation and Implementation of NCEPrimary Education Questionnaire (EIPEQ). The Questionnaire was validated by experts and a coefficient reliability of 0.75established using Crumbachs alpha method Pearson Product Moment correlation coefficient was used in analyzing the data.Result indicated that their was a significant relationship between, structural facilities, teachers qualification and text on theimplementation NCE Primary Education programme. The researchers recommended the provision of adequate facilities andemployment of specialist in the teaching of primary education studies.